PENDIDIKAN JARAK JAUH / PJJ SAAT WABAH COVID-19 MEMENGARUHI MOTIVASI BELAJAR MAHASISWA AKADEMI KEPERAWATAN HERMINA MANGGALA HUSADA - Ria Anugrahwati, Junita Maratur Silitonga (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2020)
Outbreak to Student Motivation of the Nursing Academy Hermina Manggala Husada. This study used a cross sectional study survey design on 150 student respondents. The results showed that the characteristics of the 150 respondents, mostly (95.3%) were female. Most of the respondents (96.7%) were 15-20 years old. There is a significant relationship between Distance Education and student learning motivation at the Hermina Manggala Husada Academy of Nursing, Jakarta. The recommendation of this study is the need for good communication between academic supervisors and students regarding learning motivation in PJJ and the need to create study groups so that students remain active during the Covid-19 period through online groups. Keywords : Distance Education, Covid-19, motivation to learn